Survival analysis - Odia, Isoken (Henry Stewart Talks, 2016)
Censoring, Truncation, Survival probability, Failure probability, Probability Density Function, Hazard function, Cumulative Hazard Function, Kaplan Meier, Semi-parametric, Nelson-Aalen Estimator, Log rank test, Selection Bias, Frailty models, Competing risk